PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM MATA KULIAH BAHASA INDONESIA DI PERGURUAN TINGGI - Romadani, Tiyas Fitra; Prasetyo, Danang (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2020)
AbstractThis study aims to describe the role of information and communication technology in Indonesian language learning in tertiary institutions. The research method is in the form of literature review or literature study. This research examines critically and deeply the theoretical sources associated with the problems in research. Based on the research results, the following conclusions can be drawn. (1) Information and communication technology is related to communication and information, computers, and a set of other technology-based tools that are experiencing rapid development and affecting education in Indonesia, especially in Indonesian language learning in tertiary institutions. Information and communication technology can be used as a means for compiling data and so on relating to education, especially in learning; (2) Learning has a meaning as a process to gain an experience in accordance with the purpose of a lesson, in learning Indonesian, an attractive medium is needed so that students are more interested in learning. Information and communication technology can be used as a means to increase student interest in learning Indonesian; (3) information and communication technology can be utilized in the four competencies that exist in Indonesian, namely writing, speaking, listening, and reading. Through the use of information and communication technology, it can improve the quality of lessons, student quality, student interest, and at the same time improve the quality of lecturers in technology. Â Keywords: Information and Communication Technology, Indonesian Language Learning, Higher Education